Optimalisasi Pengolahan Menu Makanan Sehat untuk Pemenuhan Gizi Anak Pra Sekolah dengan Pemanfaatan Bahan Pangan Lokal - Annisa Fitri Rahmadini; Rindasari Munir; Imas Nurjanah; Nurul Amaliyah; Riski Septiani (Lembaga Pengembangan Kinerja Dosen, 2025)
Improving the nutritional quality of early childhood plays a very important role in supporting optimal growth and development, especially in the Bogor City area which still faces stunting problems. This activity aims to increase the understanding of kindergarten teachers and parents about the importance of balanced nutrition and the use of local food ingredients as well as serving healthy and attractive food. Seminars and workshops have been carried out, covering balanced nutrition materials, cooking techniques and serving healthy food menus, and the use of local food ingredients. In addition, the application of technology is carried out through mass media, YouTube, the Healthy Child Menu (MAS) booklet and the e-Mas application to disseminate information about the importance of balanced nutrition. Evaluation of this community service activity was carried out through pretests and posttests which showed a significant increase in participant knowledge, with a T = -3.500 and p value = 0.000, meaning there is an influence of knowledge about processing healthy food menus to fulfil the nutritional needs of pre-school children. This community service activity is expected to reduce the number of malnutrition in early childhood and encourage parents to use local food ingredients as an effort to maintain children’s health in kindergarten.